Effects of olympic combat sports on physical fitness in non-athlete students: a systematic review with meta-analysis - Hernandez-Martinez, Jordan; Cid-Calfucura, Izham; Guzmán-Muñoz, Eduardo; Herrera-Valenzuela, Tomas; Delgado-Floody, Pedro; Nuñez-Espinosa, Cristian; Branco, Braulio Magnani; Mota, Jorge; Nobari, Hadi; Perez-Carcamo, Joaquin; Vásquez-Carrasco, Edgar; Valdés-Badilla, Pablo (Frontiers in Physiology, 2025)
IntroductionOlympic combat sports (OCS) present complex physical characteristics where cardiorespiratory fitness, flexibility, postural balance, endurance, agility, speed, strength, and muscular power are determinants of physical fitness. This systematic review and meta-analysis aimed to evaluate the effects of OCS interventions on selected physical fitness outcomes among school-aged and university students, compared with active or standard.MethodsA systematic literature search was conducted in May 2024 and April 2025 using seven generic databases—PubMed, ProQuest, EBSCOhost, CINAHL Complete, Scopus, Web of Science (core collection), and PEDro (Physiotherapy Evidence Database). The methodological quality and certainty of evidence were assessed using the PRISMA, TESTEX, RoB 2, and GRADE tools. The Hedge; sg effect sizes were computed. Potential sources of heterogeneity, such as subgroup analyses (type of control group, dosage training and age range), were chosen using a fixed-effects or random-effects model, with a minimum of three studies for the corresponding meta-analyses. The protocol was registered in PROSPERO (code: CRD42023391433).ResultsOf 1,539 records, 9 RCTs and 4 NRCTs with 1,314 participants were included. Six overall and three subgroup meta-analyses showed significant increases in standing long jump (ES = 1.04; p < 0.001) and sit-and-reach (ES = 0.80; p < 0.05), with no significant differences (p > 0.05) in maximal isometric handgrip strength (MIHS; ES = 0.60), Sargent jump (ES = 0.18), VO2max (ES = 0.39) and 20-m shuttle run test (ES = 0.27). While in the subgroups by dosage in sit-and-reach there were significant improvements (ES = 0.90 to 1.13; p < 0.001) in <60 min per session and according to age range in university students in favor of OCS. Meanwhile in MIHS according to control group, there were significant increases (ES = 0.21; p < 0.05) in favor of OCS versus physical education.ConclusionThe findings suggest that OCS can be a beneficial addition in standing long jump and sit-and-reach. It does not show improvements in cardiorespiratory fitness, MIHS and Sargent jump. However, with respect to dose and age range <60 min in university students is adequate to improve sit-and-reach. OCS is more effective in improving MIHS compared to physical education.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/search.